Amelia Bedelia Dances Off - Parish, Herman; Avril, Lynne 1951- (New York, NY : Greenwillow Books, an imprint of HarperCollinsPublishers, 2015)
When Amelia Bedelia's aunt gives her dance lessons as an early birthday present, she agrees to give it a try and soon finds herself making new friends and discovering that there is something to like about many different kinds of dancing.
Keywords: Dance -- Fiction; Family life -- Fiction; Friendship -- Fiction; Humorous Stories; Dance -- Juvenile fiction; Family life -- Juvenile fiction; Friendship -- Juvenile fiction; Humorous Stories; JUVENILE FICTION / Social Issues / Friendship; JUVENILE FICTION / Family / General (see also headings under Social Issues); JUVENILE FICTION / Humorous Stories